Neural, metabolic, and performance adaptations to four weeks of high intensity sprint-interval training in trained cyclists - Creer, A. R.; Ricard, M. D.; Conlee, R. K.; Hoyt, G. (International Journal of Sports Medicine, 2004)
The purpose of this study was to investigate the effects of short-term, high-intensity sprint training on the root mean squared (RMS) and median frequency (MF) derived from surface electromyography (EMG), as well as peak power, mean power, total work, and plasma lactate levels in trained cyclists when performed concurrently with endurance training. Seventeen trained cyclists were randomly assigned to a sprint training (S) group (n = 10, age 25 +/- 2.0 y) or a control (C) group (n = 7, age 25 +/- 0.5 y). Sprint training was performed bi-weekly for four weeks, comprising a total of 28 min over the training period. EMG measurements were taken before and after training during a series of four 30-s sprints separated by four minutes of active recovery. Plasma lactate, peak power, mean power, and total work were measured during each sprint bout. Following sprint training a significant increase occurred in the RMS of the vastus lateralis with a decrease in MF of the same muscle. Values for the vastus medialis did not change. Pre training exercising plasma lactate values were higher (p < 0.05) in C compared to S, but did not change with training. Exercising plasma lactate values increased (p < 0.05) from pre to post training in S, but were not different from C post training. Total work output increased from pre to post in S (p = 0.06). Peak power, mean power, and V.O (2)max increased (p < 0.05) pre to post training in S and C, indicating C was not a true control. In conclusion, these data suggest that four weeks of high-intensity sprint training combined with endurance training in a trained cycling population increased motor unit activation, exercising plasma lactate levels, and total work output with a relatively low volume of sprint exercise compared to endurance training alone.